2019
DOI: 10.1515/nanoph-2019-0377
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced terahertz emission from imprinted halide perovskite nanostructures

Abstract: Lead halide perovskites were known to be a prospective family of materials for terahertz (THz) generation. On the other hand, perovskite nanostructures, nanoantennas, and metasurfaces allow tailoring perovskites optical characteristics, resulting in more efficient interaction with incident or emitted light. Moreover, the perovskites are robust materials against formation of defects caused by mechanical deformations and can be efficiently nanostructured by various high throughput methods. In this work, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The basic properties of perovskites that make them attractive for solar cells also make them appealing for terahertz (THz) range applications [ 7 , 8 ]. Recent experiments on the generation of ultrafast photocurrents in halide perovskites excited with a femtosecond laser leading to emission of THz pulses have demonstrated the potential of these hybrid materials for THz optoelectronics [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. However, while well examined in the optical range [ 16 ], hybrid perovskites remain almost completely unexplored for THz applications.…”
Section: Introductionmentioning
confidence: 99%
“…The basic properties of perovskites that make them attractive for solar cells also make them appealing for terahertz (THz) range applications [ 7 , 8 ]. Recent experiments on the generation of ultrafast photocurrents in halide perovskites excited with a femtosecond laser leading to emission of THz pulses have demonstrated the potential of these hybrid materials for THz optoelectronics [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. However, while well examined in the optical range [ 16 ], hybrid perovskites remain almost completely unexplored for THz applications.…”
Section: Introductionmentioning
confidence: 99%
“…Korolev et al reported using nanoimprint lithography to enhance THz emission from MAPbI 3 perovskite upon femtosecond laser irradiation. The efficiency of THz emission from the nanostructured perovskite was enhanced by 3.5 times as compared with a smooth perovskite film [70]. In 2020, Cheng et al coated THz antenna by an epsilon-near-zero (ENZ) metamaterial superstrate showed in Fig.…”
Section: Optimization Of Thz Systemmentioning
confidence: 99%
“…[ 15 ] Many measures have been considered to resolve this, and various methods have been attempted, ranging from printing patterns with stamps to the use of lasers and inkjets. [ 16–33 ] These methods are presented in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…
considered to resolve this, and various methods have been attempted, ranging from printing patterns with stamps to the use of lasers and inkjets. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] These methods are presented in Figure 1.In this article, we describe the perovskite patterning method, in two sections. In the first section, we briefly introduce the traditional perovskite patterning method employing PRs.
…”
mentioning
confidence: 99%
See 1 more Smart Citation